Wearable and flexible sensors for user-interactive health-monitoring devices. Issue 24 (6th June 2018) - Ha, Minjeong; Lim, Seongdong; Ko, Hyunhyub
Abstract : The development of flexible and wearable healthcare devices facilitates a real-time monitoring of body activities as well as detecting various biosignals, which provided useful information to manage one's health condition for personal health monitoring. Abstract : Flexible electronic devices that are lightweight and wearable are critical for personal healthcare systems, which are not restricted by time and space. To monitor human bio-signals in a non-invasive manner, skin-conforming, highly sensitive, reliable, and sustainable healthcare monitoring devices are required. In this review, we introduce flexible and wearable sensors based on engineered functional nano/micro-materials with unique sensing capabilities for detection of physical and electrophysiological vital signs of humans. In addition, we investigate key factors for the development of user-interactive healthcare devices that are customizable, wearable, skin-conforming, and monolithic (design), and have long-term monitoring capability with sustainable power sources. Finally, we describe potential challenges of developing current wearable healthcare devices for applications in fitness, medical diagnosis, prosthetics, and robotics.